COMBINING ABILITY FOR FLOWERING AND YIELD TRAITS OF JATROPHA (Jatropha curcas L) (Bangladesh Journal of Plant Breeding and Genetics, 2017)
An experiment was conducted with 6 × 6 half diallel population to determine the combining ability for yield characters in Jatropha. Combining ability analysis revealed that both general and specific combining ability variances were significant for all the characters studied. GCA was observed to be higher in magnitude for majority of the characters except number of inflorescence per plant indicating that these characters were predominantly under additive genetic control. The non additive components of variance were also involved in the inheritance of number of inflorescence per plant. The parent P1 was the best general combiner for most of the traits including earliness and seed yield per plant and P5 was the poor general combiner for all the traits except hundred seed weight. Higher negative SCA effect was found in the cross combination P1×P3 for earliness and positive effect for seed yield per plant. Finally, it can be concluded that both additive and dominant genetic components are important for earliness and seed yield in Jatropha. The cross combination P1×P2, P1×P3, P2×P5 and P4×P6 is found promising for earliness and seed yield per plant. These combinations could be selected for the development of hybrid varieties in Jatropha.